1997
DOI: 10.1177/002215549704500711
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Expression of C-CAM in the Rat Placenta

Abstract: We investigated the expression of the immunoglobulin superfamily cell adhesion molecule, C-CAM, in developing and mature rat placenta. By immunohistochemical staining at the light microscopic level, no C-CAM-expression was seen before Day 9 of gestation, when it appeared in the trophoblasts of ectoplacental cones. On Day 10.5, spongiotrophoblasts and invasive trophoblasts around the maternal vessels of the decidua basalis were stained positively. On Day 12.5, C-CAM was detected in the spongiotrophoblasts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…In adult tissues the CEA-related cell surface molecules are expressed primarily in different epithelia, vessel endothelia, and hematopoietic cells [11][12][13][14][15], but individual molecules show distinct expression patterns. The spatiotemporal expression pattern of C-CAMs suggests important functions during embryonic development; a highly dynamic expression has been seen in, for example, the trophoblasts of the placenta [16,17], the endothelial cells and pericytes during vascularization of the central nervous system [18], muscle development [16], and development and eruption of teeth [19].…”
Section: Cell Surface Cea Family Molecules Are Multifunctionalmentioning
confidence: 99%
“…In adult tissues the CEA-related cell surface molecules are expressed primarily in different epithelia, vessel endothelia, and hematopoietic cells [11][12][13][14][15], but individual molecules show distinct expression patterns. The spatiotemporal expression pattern of C-CAMs suggests important functions during embryonic development; a highly dynamic expression has been seen in, for example, the trophoblasts of the placenta [16,17], the endothelial cells and pericytes during vascularization of the central nervous system [18], muscle development [16], and development and eruption of teeth [19].…”
Section: Cell Surface Cea Family Molecules Are Multifunctionalmentioning
confidence: 99%
“…Its initial discovery was as a biliary glycoprotein that is present in the bile in association with expression on the hepatocyte membrane [2][3][4]. CEACAM1 expression occurs as early as embryonic development where it is found on trophoblasts of both the pre-implanting embryo, placenta and infiltrating leukocytes [5][6][7]. CEACAM1 also exhibits either constitutive (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We and others reported that the IgSF molecule carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is associated with early stages of angiogenesis: CEACAM1 is expressed in newly formed blood vessels on the fetal-maternal interface in both rodents and humans; on microvessels of a variety of human tumors and of regenerating tissues, such as endometrium or granuloma tissue after wounding; on endothelial progenitor cells; and in stenotic aortic valve tissue (12)(13)(14)(15)(16). Notably, CEACAM1 exhibits a disease-specific expression pattern on tumoral endothelium in vivo, as demonstrated by Oh et al (17), and appears to be involved in vascular reprogramming in Kaposi sarcoma (18).…”
Section: Introductionmentioning
confidence: 99%